Semiotic information in data-driven societies: Where are we heading to? - Rodrigues, Mariana Vitti; Gonzalez, Maria Eunice Quilici (SAGE Publications, 2018)
What is the role of information in autonomous action in data-driven societies? This question is addressed in the present paper, which aims to discuss the role of information in the dynamics of habits that guide action. A naïve map of contemporary approaches to information is proposed, with indications of the challenges faced by each of them. From the proposed map, we claim that the Peircean semiotic approach to information, which brings ethical and aesthetic principles, sheds light on analyses of complex problems faced by contemporary data-driven societies. Examples of topics discussed are autonomous action and privacy in self-tracking activities, healthcare records, and genetic identification.
Keywords: Autonomous action; Data; Information; Semiotics